Optimizing Teaching Workshops to Advance the Competencies of Islamic Religious Education Lecturers in the Integration of Digital Technology - Santalia, Indo; Satriani, Satriani; Muhsyanur, Muhsyanur (ETDC: Indonesian Journal of Research and Educational Review, 2023)
This article evaluates and optimizes the implementation of teaching workshops aimed at improving the competencies of Islamic Education (PAI) lecturers in using digital technology at the Islamic Institute of As'adiyah Sengkang. The study focuses on understanding how workshops can enhance PAI lecturers' digital technology skills and identifying strategies to optimize the workshops for more effective technology adoption. A descriptive qualitative method, including interviews and observations, was used for data collection. The hermeneutic approach provided insights into the lecturers' experiences regarding the workshops and the integration of technology in teaching. Findings indicate that although the workshop materials were relevant, additional practice time and simplified content are necessary to improve lecturers' understanding. While there was a noticeable increase in competencies, technical challenges still exist, requiring continuous support. Optimizing the workshops involves adding more practice sessions, simplifying content, and offering mentorship to build lecturers' confidence in implementing digital technology effectively. This research provides valuable insights for enhancing the development of digital competencies among PAI lecturers.